Willingness to start insulin therapy among insulin-naïve persons with type 2 diabetes mellitus at Gulu Regional Referral Hospital, Gulu City, Uganda - Nakitto, Brenda; Opedo, Moses; Nansubuga, Federes; Omondi, Edward; Musinguzi, Emmanuel; Otile, Edwin Cleopas; Ekak, Steven; Nannungi, Christine; Apiyo, Paska; Pebolo, Pebalo Francis; Bongomin, Felix (SAGE Publications, 2024)
Exploring readiness for insulin treatment in people with type 2 diabetes at Gulu Regional Referral Hospital, Uganda In this study, we investigated the willingness to start insulin therapy among individuals with type 2 Diabetes Mellitus (DM2) in urban Northern Uganda. Understanding the importance of insulin for glycemic control in DM2, we surveyed 190 participants at Gulu Regional Referral Hospital. We found that more than three-quarters of the participants expressed a willingness to receive insulin therapy if recommended. Factors influencing this willingness included recent advice on insulin, which was associated with a 34% higher likelihood of acceptance. Conversely, individuals with a disease duration of 6 years or more were 43% less willing, and those concerned about coping with insulin therapy were 55% less willing to commence treatment. These findings underscore the need for healthcare providers to offer personalized counseling strategies, addressing specific concerns, to facilitate informed decision-making regarding insulin initiation. Looking ahead, interventions should prioritize overcoming barriers related to prolonged disease duration and apprehensions about insulin therapy to optimize glycemic control and improve the well-being of individuals with DM2 in this population.
Keywords: diabetes mellitus, Gulu, insulin naïve, willingness